2001
DOI: 10.1097/00004728-200101000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Cervical, Thoracic, and Lumbar Bone Mineral Density by Quantitative CT

Abstract: Trabecular BMD of C2 and C5 measured by QCT is significantly higher than trabecular BMD of T12 and L4 in nonosteoporotic volunteers of both genders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
3
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 32 publications
3
36
3
6
Order By: Relevance
“…The question that arises is whether these densitometric data may be used for accurate BMD assessment. Preliminary studies have shown that high correlation between BMD, as determined with routine abdominal CT, versus lumbar QCT can be achieved [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The question that arises is whether these densitometric data may be used for accurate BMD assessment. Preliminary studies have shown that high correlation between BMD, as determined with routine abdominal CT, versus lumbar QCT can be achieved [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Yoganandan et al 12) reported that the mean BMD of the third cervical vertebra in young healthy adult female volunteers was 264.7 mg/ml. Also, Weishaupt et al 19) reported that the mean BMD of the second cervical vertebra in young healthy adult female volunteers was 297.2 mg/cm 3 . The mean BMD (255 mg/cm 3 HA) of the third cervical vertebra in the normal group of the study was Yoganandan et al 11) reported that the correlation coefficients between the BMDs of the cervical and lumbar vertebrae ranged from 0.615 to 0.757 in young healthy adult male volunteers.…”
Section: Discussionmentioning
confidence: 98%
“…The correlation coefficients in young healthy adult female volunteers ranged from 0.330 to 0.667, and the correlation coefficients of super-cervical vertebrae were lower than those of inferior cervical vertebrae 12) . Also, Weishaupt et al 19) reported that the correlation coefficient between the second cervical and fourth lumbar vertebrae in young healthy adult female volunteers was 0.379. In the present study of postmenopausal women, the correlation coefficient was 0.705, with the value being in the range of young healthy adult male volunteers 10) .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported the differences in tBMD values throughout the lumbar, thoracic and cervical spine in human medicine. One study showed that mean tBMD values for women and men at the T12 vertebra (193.1/184.9 mg/cm 3 ) were higher than those at the L4 vertebra (186.2/180.1 mg/ cm 3 ) [28]. Another study revealed that the mean tBMD value at the T1 vertebra was higher than that at the L2 through L4 vertebrae in healthy female adults [29].…”
Section: Discussionmentioning
confidence: 99%